2011
DOI: 10.1037/a0023992
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of motivational interviewing interventions for adolescent substance use behavior change: A meta-analytic review.

Abstract: The effectiveness of MI interventions for adolescent substance use behavior change is supported by this meta-analytic review. In consideration of these results, as well as the larger literature, MI should be considered as a treatment for adolescent substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
207
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(236 citation statements)
references
References 46 publications
(27 reference statements)
17
207
3
8
Order By: Relevance
“…However, the eff ects were observed in the groups where the follow-up was implemented between one to three months after the fi rst intervention, and not in those groups where the follow up exceeded three months. These results are similar to those found elsewhere (e.g., Jensen et al, 2011;Lundahl et al, 2010;Moyer et al, 2002;Vasilaki et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the eff ects were observed in the groups where the follow-up was implemented between one to three months after the fi rst intervention, and not in those groups where the follow up exceeded three months. These results are similar to those found elsewhere (e.g., Jensen et al, 2011;Lundahl et al, 2010;Moyer et al, 2002;Vasilaki et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Notwithstanding, they are likely to be infl uenced by the time elapsed between sessions, and the number of sessions (Jensen et al, 2010;Lundahl et al, 2010). Jensen et al (2011) found that when the time intervals between MI interventions are of less than six months, there is a greater eff ect than in those cases with longer periods of time. For BI, Moyer, Finney, Swearingen, & Vergun (2002) reported that the eff ect decreases when the time between the fi rst intervention and the follow-up is longer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of the literature indicate brief interventions using motivational interviewing are effective in reducing adolescent substance use (Barnett, Sussman, Smith, Rohrback, & Spruijt-Metz, 2012;Jensen, Cushing, Aylward, Craig, Sorell, & Steele, 2011;Tevyaw & Monti, 2004). However, a close examination of the studies reviewed indicates limited research examining interventions specific to 9 th grade students.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests prevention programs using brief motivational enhancement approaches with individualized feedback are effective in reducing adolescent drinking (Barnett et al, 2012;Jensen et al, 2011;Tevyaw & Monti, 2004). Although no efficacy trials have been conducted with the eCHECKUP TO GO with high school students, several studies have demonstrated the efficacy of the eCHECKUP TO GO among college students, including first year students (Doumas & Anderson, 2009;Doumas, Kane, Navarro, & Roman, 2011, Doumas, Nelson, DeYoung, & Conrad, in press;Hustad, Barnett, Borsari & Jackson, 2010;Walters, Vader & Harris, 2007), student athletes (Doumas, Haustveit, & Coll, 2010), and students sanctioned for campus alcohol policy violations (Alfonso, Hall & Dunn, 2012;.…”
Section: Interventionmentioning
confidence: 99%